Evaluation of bovine uterine gland functions in 2D and 3D culture system - Yosuke SUGINO; Taiki SATO; Yuki YAMAMOTO; Koji KIMURA (The Society for Reproduction and Development, 2022)
In ruminants, uterine glands play key roles in the establishment of pregnancy by secreting various factors into the uterine lumen. Although a three-dimensional (3D) culture system has been used for investigating cellular functions in vitro, the detailed functions of uterine gland have not been fully elucidated. In this study, we examined the benefits of 3D culture system to examine the innate functions of bovine uterine glands. Isolated bovine uterine glands were cultured on Matrigel (2D) or in Matrigel (3D), respectively, and the mRNA levels of secreted proteins (SERPINA14, MEP1B, APOA1, ARSA, CTGF, and SPP1) were measured in isolated and cultured uterine glands. The protein expression of estrogen receptor β (ERβ) and progesterone receptor (PR) and the establishment of apico-basal polarity were examined. In isolated uterine glands, the mRNA levels of secreted proteins changed during the estrous cycle. Although uterine glands cultured in both 2D and 3D expressed ERβ and PR, progesterone did not affect SERPINA14 mRNA expression. The expression of APOA1 mRNA in 2D cultured uterine glands did not respond to estrogen and progesterone. Additionally, the mRNA levels of secreted proteins in the 3D culture system were significantly higher than those in the 2D culture system, which might be attributed to the different cellular morphology between them. The locations of ZO-1 and β-catenin in 2D cultured uterine glands were disordered compared with 3D cultured uterine glands. These results showed that the hormonal responsiveness of secreted factor expression and cellular morphology were different between 2D and 3D cultured bovine uterine glands.